Complementary therapies intervention in Parkinson’s disease: systematic review and meta-analysis - Sabbadin, Fabio; Geraci, Michela; Nieddu, Laura; D’Imperio, Daniela; Pregnolato, Giorgia; Cacciante, Luisa (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by both motor and non-motor impairments, leading to significant declines in quality of life (QoL). While physiotherapy remains a mainstay of non-pharmacological management, interest in complementary therapies—such as music therapy, dance, and art therapy—has grown due to their potential to address motor, cognitive, emotional, and social aspects of PD within a holistic framework.ObjectiveTo evaluate the effectiveness of complementary therapies compared to usual care (e.g., physiotherapy) in improving balance, functional mobility, freezing of gait (FOG), and QoL in individuals with PD.MethodsA systematic review and meta-analysis was conducted following PRISMA guidelines and registered in the PROSPERO database (registration code: CRD42025636700). Search was performed on PubMed, Cochrane, Web of Science, and Embase. Eligible studies included randomized or quasi-randomized controlled trials and clinical controlled trials comparing complementary therapies (e.g., music, dance, drama) to usual care in individuals with PD. Primary outcome was balance, whereas functional mobility, FOG, and QoL were set as secondary outcomes. Risk of bias was assessed using the Cochrane RoB2 tool and meta-analyses were performed.ResultsOut of 723 identified records, 29 studies met inclusion criteria and were included for qualitative synthesis. Among these, 17 studies were included in the meta-analysis, whereas risk of bias was performed on 29 studies, revealing scarce methodological quality of the included studies. Balance and functional mobility meta-analyses showed a significant benefit of complementary therapies over usual care.ConclusionComplementary therapies demonstrate moderate evidence of benefit in improving balance and functional mobility in individuals with PD, with less conclusive evidence for QoL and FOG. High heterogeneity and methodological limitations across studies highlight the need for more rigorous research.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42025636700.